The correlation between the use of implant contraception the weight change and the disturbance of the menstrual cycle around puskesmas padamara - Laelah, Nur; Aprilina, Happy Dwi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Â Background: Contraception Implants are contraceptive devices in the form of Silastic capsules containing synthetic progesterone-type hormones implanted under the skin, with the top consisting of 6 capsules measuring approximately 3 cm containing levonorgestrel. The advantages of implants are very effective in pregnancy. The success rate is among 100 implant KB users (Keluarga Berencana) or widely known as the family planning program in Indonesia. The disadvantage of the implanted birth control method is that it triggers an increase or decrease in body weight and changes in the menstrual cycle.Objective: To determine the changes and correlation between changes in body weight and menstrual cycle disorders on implantable KB users.Method: This study used a cross-sectional approach using univariate and bivariate analysis methods. A simple random sampling technique was used as the sampling technique in this research. The number of samples in this research was 73 people. Questionnaires and adult body scales were used to collect the data. The data were analyzed using Chi Square test.Results: There were 34 people (46.6%) who experienced weight change and experienced a weight gain. In addition, there were as many as 43 people (58.9%) who experienced menstrual cycle disorder in term of polimenorea . There was a correlation between the use of an implant with changes in body weight (p = 0.03), menstrual cycle disorders (p = 0.00).Conclusion: The use of implants changes in body weight and menstrual cycle disorders.